Spilled milk and burned toast: extrinsic pressure and sporting excellence. Issue 2 (4th May 2021) - Johnson, Christopher; Taylor, Jason
ABSTRACT: This paper explores the dynamics of extrinsic pressure in sport and its relation to athletic excellence. We argue that psychological pressure exerted by activities extrinsic to sport can be relevant to success or failure in it, such that how one manages extrinsic pressures can transmit to failure to perform in sport and thus be a determinant to victory, with no reason to think failure mitigated by the non-sporting nature of one's other behaviour. To make this argument we offer a series of examples to test intuitions about what constitutes sporting excellence and what constitutes sporting failure. On the basis of these examples, we offer a categorization of pressures in sport and argue that psychological pressure from almost any area of life may be relevant to competition, whether intrinsic or extrinsic to the sporting contest. We substantiate this claim by proposing a framework for adjudicating the relevance of extrinsic pressures to sporting performance by appealing to the internal goods of each sport and their contribution to flourishing.